Proceso de atención nutricional en paciente masculino de 50 años de edad de pancreatitis necrotizante. - Murillo Suarez, Estrella Deyaneira (2024)
A 50-year-old patient was diagnosed with necrotizing pancreatitis. The clinical history was characterized by severe abdominal pain, nausea, and loss of appetite. Initial evaluation revealed a BMI of 26.1, indicating overweight, and waist and hip circumferences of 95 cm and 105 cm, respectively, with a waist/hip ratio of 0.90. Patient management included a specific nutritional plan to minimize pancreatic stress and reduce inflammation. The diet was carefully balanced to provide the necessary amount of nutrients without overloading the pancreas. The plan included a moderate intake of protein (88.77 g), healthy fats (31.80 g) and carbohydrates (169.67 g), spread over five meals a day to aid digestion and glucose control. Monitoring of the patient's progress was essential to adjust the plan according to his clinical response. Symptoms such as abdominal pain and nausea were evaluated, as well as clinical parameters such as blood pressure and blood sugar levels. Follow-up showed a significant reduction in symptoms and stabilization of clinical parameters. Implementation of the diet plan resulted in an overall improvement in the patient's health status and highlights the importance of a comprehensive approach in the treatment of necrotizing pancreatitis. Adequate patient education on the importance of following the diet plan and regular follow-up visits were key to compliance and long-term success. Careful planning and adherence to the diet plan allowed for effective treatment of necrotizing pancreatitis, which significantly improved the patient's quality of life and reduced the risk of complications.